1996
DOI: 10.1159/000262158
|View full text |Cite
|
Sign up to set email alerts
|

Grey Discolouration for the Diagnosis of Secondary Caries in Teeth with Class II Amalgam Restorations: An in vitro Study

Abstract: Grey discolouration around occlusal amalgam restorations has been found to be useful for the diagnosis of secondary caries. The aim of the present in vitro study was to establish the validity of grey discolouration of buccal and lingual enamel next to the approximal amalgam of class II restorations for the diagnosis of secondary caries. One hundred buccal and lingual areas next to the approximal parts of a class II filling in molars and premolars were included in the study. Fifty-one areas showed grey discolou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

1998
1998
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
0
4
1
Order By: Relevance
“…This fact contributes to emphasize the lower reliability of the tested methods. 24 Hence, tactile examination and radiography would not be the most appropriate methods to detect secondary caries at the dentine threshold, which disagrees with previous findings related to radiographic examination, 7,11,25 but agrees with previous results related to tactile examination. 26 Despite the limitation of the visual index used in detecting early secondary caries due to the difficulty in distinguishing discolorations originated from the restoration or from demineralizations, 6 the visual inspection presented the highest sensitivity Table 1 -Sensitivity, specificity and accuracy of the laser fluorescence, visual inspection, radiography and tactile examination methods for detecting secondary caries lesions in primary teeth at enamel (D2) and dentine (D3) thresholds, and their performance expressed as the area under the ROC curve (Az).…”
Section: Discussioncontrasting
confidence: 59%
“…This fact contributes to emphasize the lower reliability of the tested methods. 24 Hence, tactile examination and radiography would not be the most appropriate methods to detect secondary caries at the dentine threshold, which disagrees with previous findings related to radiographic examination, 7,11,25 but agrees with previous results related to tactile examination. 26 Despite the limitation of the visual index used in detecting early secondary caries due to the difficulty in distinguishing discolorations originated from the restoration or from demineralizations, 6 the visual inspection presented the highest sensitivity Table 1 -Sensitivity, specificity and accuracy of the laser fluorescence, visual inspection, radiography and tactile examination methods for detecting secondary caries lesions in primary teeth at enamel (D2) and dentine (D3) thresholds, and their performance expressed as the area under the ROC curve (Az).…”
Section: Discussioncontrasting
confidence: 59%
“…Observing the relationship between bluish-grey staining and dentinal demineralization, even when using different indicators, it could be concluded that the color adjacent to a restoration was a poor criterion to predict a subjacent dentinal exposure (4,17). On the other hand, the absence of staining represents a good indicator of the absence of disease (18). For the ditching criterion, the sensitivity (s=0.27) and the PPV (0.46) were low; whereas the NPV was only moderate (0.64).…”
Section: Indicatormentioning
confidence: 99%
“…Color change has been found to be irrelevant to the degree of infection of the tissue beneath the restorations; thus, color change should probably be disregarded in the diagnosis of secondary caries beneath amalgam restorations [Kidd et al, 1995]. On the other hand, while Rudolphy et al [1996] found that gray discoloration was not useful for the detection of secondary caries, they found that the absence of gray discoloration was a good predictor for the absence of secondary caries. In the present study, by changing the VC cutoff to 2, which included gray and blue discoloration as sound, sensitivity became lower and PPV showed a similar pattern to VC cutoff 0 at all CLSM thresholds.…”
Section: Visual: Color Change (Vc)mentioning
confidence: 99%